Answer:
-2
Step-by-step explanation:
Add 5 to both sides to get
3x-5+5=-11+5
and simplify to get
3x = -6
x = -2
Answer:
magic
Step-by-step explanation:
that is a magic childerns are just biting and spliting the apples
Answer:
Step-by-step explanation:
Instead of dividing both sides by 5, it is multiplied
5x + 3 = 6 {Subtract 3 from both sides}
5x + 3 - 3 = 6-3
5x = 3 {Divide both sides by 5}
5x/5 = 3/5
x = 3/5
So, when adding in the 7 and 3 the new equation is:
9{(9x7)+(4x3)+9}
Following pemdas, you have to do parenthesis first. So now the equation is:
9(63+12+9)
Now distribute the 9:
567 + 108 + 81
And finally solve as a normal addition problem:
567 + 108 + 81= 756
So, the answer is 756.
I hope this helps:)